Kakas Bantu Perhitungan Nilai Reusability Berdasarkan Rancangan Perangkat Lunak - Rosita Budianti; Fajar Pradana; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Reusability is one of the software quality that means the ability to reuse software components on other problems to reduce time, cost, and human resources. Reusability can be measured at the design phase so the software design can be improved as early as possible before it is implemented. This research is intended to develop a tool for measuring reusability of software design automatically. Measurement of reusability is done by multiple regression techniques using object oriented design property metrics, namely coupling, encapsulation, and inheritance based on the Quality Model for Object-Oriented Design (QMOOD) metric, because the correlation between reusability and property has been validated and results in high acceptance values of 95%. Reusability is calculated from the input class xml diagram. From the results of development, all defined requirements have been tested and produce valid. In addition, for efficiency requirements, the system has efficiency that is 100% can do calculations and time is faster than manual calculations for both simple and complex test filed. So the system can be useful to help calculate reusability more efficiently than manual counting.